EVALUASI KINERJA SLURRY SEMEN PADA PEKERJAAN CEMENT SQUEEZE BERDASARKAN UJI RHEOLOGI, THICKENING TIME, DAN COMPRESSIVE STRENGTH - Lia Mega; Sri H. Mayaut; Sandro C. Pattipawaej; Havidh Pramadika; Geovanny B. Imasuly (Petro : Jurnal Ilmiah Teknik Perminyakan, 2026)
The cement squeeze operation is an important remediation method for repairing casing leaks and restoring zonal isolation in problematic wells. This study aims to evaluate the performance of cement slurry used in cement squeeze operations under High Temperature High Pressure (HTHP) conditions through rheological, thickening time, and compressive strength tests. The slurry formulation utilized API Class G cement enriched with 35% BWOC silica flour (SCSR-75), with the addition of antifoam (SAL-01L), dispersant (SCD-01L), fluid loss additive (SFL-01L), gas block additive (SBA-01L), and high-temperature retarders (SRD-01L and SRD-05L) to maintain stability during pumping and setting. Rheological testing indicated that the slurry exhibited stable flow behavior, with acceptable plastic viscosity for both the lead and tail slurries, demonstrating good pumpability without loss of stability. Thickening time tests showed a setting time of 6–7 hours at 216 °F, which remains within a safe operational window for pumping. Meanwhile, compressive strength testing revealed an increase in compressive strength from 500 psi to 1,638 psi within 24 hours at 260 °F. These results confirm that the combination of lead and tail slurry systems with the selected additive configuration delivers optimal cement performance in HTHP environments.